Technological tools and development of ict skills in teachers at UNHEVAL - Huánuco 2021 - Ascayo León, Orlando (2022)
The research line of this work is framed in educational sciences, and as a sub-line of research: Relevant and quality learning. This research has focused on the application of the BIOLAB program and the development of meaningful learning in a remote classroom context due to the health emergency caused by the COVID-19 pandemic. The objective of this research has been to evaluate the influence of the BIOLAB program on the development of meaningful learning in university students. The methodology of this work belongs to the quantitative approach, of the applied type; The techniques with which the information was collected was the questionnaire with pre-test and post-test to the control group and the experimental group. The results of the study determined that the application of the BIOLAB program improves the level of meaningful learning in students by 70%. Therefore, it is determined that the application of the BIOLAB program significantly influences the improvement of meaningful learning.